Open Access Library and Information Science journals: an analysis of the adopted business models (Perspectivas em Ciência da Informação, 2022)
This study investigates the business models practiced by open access scientific journals in the area of Library and Information Science, indexed in the Directory of Open Access Journals (DOAJ). We did an exploratory study of the theme, combining quantitative and qualitative approaches, and applying the documentary method. The data were collected in the DOAJ, retrieving the journals of Library and Information Science that are indexed in the filter "Bibliography. Library science. Information resources", followed by a visit to each journal's website to identify descriptive characteristics. Content analysis was used to evaluate and categorize the data collected. As a result, it was verified that most of the journals retrieved in the filter do not charge Article Processing Charges (APCs), and that of those that do, a considerable portion use the 'Publishing Rates' business model with discount policies and/or fee exemptions. It is concluded that this theme has different perspectives when considering the financial sustainability of a journal, with advantages and disadvantages, mainly regarding the authors of articles to be submitted in journals that use APCs.